Insights from positive deviance approach to support socially inclusive climate adaptation in Kenya dairy systems - Bullock, Renee; DuttaGupta, Tanaya; Miriti, Philip (International Livestock Research Institute, 2023)
Transformation to climate-smart livestock systems can generate multiple trade-offs and synergies. In Kenyan dairy farming systems, gender norms and practices influence ownership and decision-making about information, innovations, and labor. Positive deviance is used to identify common practices and deviations from those practices in dairy households. The approach provides the opportunity to learn about ‘hidden’, less socially acceptable behaviors.